Experimental research on the pressure and flame propagation behaviors of LPG-air mixtures in a double obstructed tube. (April 2023) - Wang, Tao; Yi, Weizhai; Liang, He; Yang, Peng; Luo, Zhenmin; Sun, Lu; Cheng, Fangming; Kang, Xiaofeng; Feng, Zairong; Deng, Jun
Abstract: To comprehensively identify the deflagration propagation characteristics of LPG-air mixtures under obstacle conditions, in the present work, repeat rectangular obstacles with block ratios ranging from 0.1 to 0.9 and six kinds of obstacles with different shapes at a block ratio of 0.6 were selected. Their influence on the deflagration characteristics of LPG-air with volume fractions from 4% to 8% was experimentally investigated in a closed tube with a length-to-diameter ratio of 20.4. The deflagration pressure parameters, the evolution of the flame front, and the flame speed were obtained and analyzed. The results show that the repeat rectangular obstacles increase Pmax and the revised deflagration indexes, shorten the time to reach the maximum pressure, and greatly increase the LPG-air explosion hazard level. The repeat rectangular obstacles at a block ratio of 0.6 elevate the explosion of LPG explosion the most. Due to the different turbulence levels induced by the repeated obstacles with various shapes, there are differences in their enhancement effect. The turbulent combustion of the flame in the vortex region between the obstacles greatly promotes the flame propagation speed. The results obtained from this work are significant in providing fundamental data on LPG explosions, providing guidance for the design of LPG-related devices and structures, and developing more effective explosion protection measures. Highlights: Repeat rectangular obstacles at block ratio of 0.6 elevate the LPG explosion most. The repeat mesh square obstacle has the weakest promoting effect on the Pmax of LPG. Turbulent combustion in the vortex region between the obstacles greatly promotes the flame speed.